Force transmission of flexure-based leverage mechanism for static unbalance measuring system under self-gravity effect - Yan, Weixin; Liu, Jihao; Guan, Enguang; Yan, Ning; Zhao, Yanzheng (Advances in mechanical engineering, 2017)
This article proposes a flexure-based leverage mechanism that improves the performance of the static unbalance measurement system in terms of sensitivity and precision. The primary function of the flexure-based leverage mechanism is to transform the objective unbalance force/moment from the double-frame platform to an electromagnetic force balance sensor. A model of the flexure-based leverage mechanism was established to investigate the displacement/force amplification based on the elastic model. The finite element method was used to verify the analytical solutions. Considering the gravity effects, the self-weight of the rigid bodies in this leverage mechanism has an effect on the reading in the sensors. However, the linearity characteristics are not sensitive to the self-weight of the proposed leverage mechanism and the stiffness of the flexure hinges. Virtual experiments conducted to verify the linearity and sensitivity of the system indicated that depending on the leverage function of the flexure-based leverage mechanism, the systematic sensitivity is less than 0.02 g/(g cm), the resolution is 0.0013 g cm, and the maximum linearity error is 2.7%.